Reactance to Transgressors: Why Authorities Deliver Harsher Penalties When the Social Context Elicits Expectations of Leniency - Moore, Celia; Pierce, Lamar (Frontiers in Psychology, 2016)
This paper combines experimental and field data to examine how authorities with discretion over how rules are enforced penalize transgressors when the social context of the transgression elicits expectations of leniency. Specifically, we test how transgressors are punished when it is their birthday: a day that triggers expectations of lenient treatment. First, in three scenario studies we explore individuals’ intuitions about how they would behave and expect to be treated if they transgressed on their birthdays, as well as how they would imagine penalizing a birthday transgressor. Second, using more than 134,000 arrest records for drunk driving in Washington State, we establish that police officers penalize drivers more harshly when it is their birthday. Then, in a lab experiment in which we grant participants discretion over enforcing the rules of an essay-writing contest, we test psychological reactance towards transgressors who make their birthday salient, even subtly, as the mechanism behind this increased stringency. We rule out several alternative explanations for this effect, including public safety concerns, negative affect and overcompensation for bias. We conclude with a discussion of the theoretical and practical implications of our findings for the literatures on punishment, rule-breaking, and legal transgressions.